Genome editing to re-domesticate and accelerate use of barley crop wild relatives - Hanak, Tobias; Janjić, Jovana; Hay, Fiona R.; Brinch-Pedersen, Henrik (Frontiers in Sustainable Food Systems, 2023)
Climate change threatens global food security, but the biggest impact will be in arid, low social-economic regions. To improve food security, new breeding technologies (NBTs) could be implemented for re-domestication of crop wild relatives (CWR). CWR harbor many beneficial traits, but it is difficult to incorporate these traits into conventional breeding programs. Thus, although genebanks hold significant collections of CWR, their potential has yet to be reached. Using barley as an example, we describe how using genebank collections, digital sequence information and NBTs, re-domesticated barley can be produced with improved characteristics, while retaining the resilience and adaptation of the original material. Lastly, we highlight some obstacles that need to be overcome for re-domesticates to be adopted.